SECURITY THREATS FORMS IN THE CONTEXT OF PRIVATE PROTECTION OF PEOPLE AND PROPERTY (Security Dialogues, 2024)
This paper will present different forms of endangering security from the aspect of discussion in the protection of people and property. In today’s time of technological development, liberalization of the public security sector and physical border security, the setting of democratic standards has opened up large gaps to which the state sector does not have an adequate response. The answer lies in expensive technical equipment and practical training of personnel, which, however, many countries cannot afford. In addition, different interpretations of legal provisions, lack of competent personnel, although officially there are qualified personnel, in addition to that open space, allows various forms of endangering security in the interior of the state territory, and increasingly demanding challenges are posed to various security subjects. In order to protect people and property, the private security sector has been imposed, which often grows into private armies, which we havein the examples of the former Balck Waters, or Academi, up to today’s Wagner group. The main goal of this paper is to show the forms of threats to security, and to set the limits of engagement of private agencies for the security of property and persons. The subject of the work is the classification of security threats. The problem of this work arises from the subject, and it refers to the correct detection of threats to security, which contributes to the adequate reaction of security entities. This work has universal significance because it is about general,universal forms of security threats that can happen anywhere and anytime. Especially the countries of the Balkans are vulnerable, given the results of the post-socialist tradition. Therefore, it is not necessary to give a spatial and temporal determination of the processing of the mentioned topic. Nevertheless, a review of the topic of the importance of endangering security is from Bosnia and Herzegovina, where it is a decentralized state with decentralized security authorities that are very often an obstacle to achieving complete security or a more or less high level of security.
Keywords: security, endangerment, criminality, sources, forms